Barriers to industrial energy efficiency : a literature review - Sorrell, Steve (UNIDO ViennaAT, 2011)
Proposes to identify the nature, operation and determinants of different barriers to the adoption of energy efficient technologies in industry; assesses the prevalence and relative importance of these barriers in different contexts; and provides a springboard to determine where to most effectively address policy efforts.